The study on impacts of strategic planning at Malaysian Airlines Cargo Sdn Bhd (MASkargo) Malaysia / Mohamad Fais Mohd Durahim - Mohd Durahim, Mohamad Fais (Faculty of Business and Management, 2011)
The purpose of this study is to indicate impact of strategic planning in MASkargo business cycle. It is the further investigation of the result of strategic planning in all the business activities. In this study it will help the organization to ensure the correct action in the industry. The issue of strategic planning is significantly importance as it is the indicators of the right actions. As the region enters the digital 21st century with new economy, all organizations are looking forward to upgrade their businesses and lay down the strategic planning to make known of their existence in the globalize and challenging industry. Therefore this paper discusses the result of implementation of strategic planning which are beneficial toward the company. Analysis of survey responses based on 50 respondents from position executive and non-executive different department found that most of the variables in the study significantly contributed towards the implementation of strategic planning in MASkargo Sdn Bhd.